Tinjauan Yuridis terhadap Pertanggungjawaban Pidana dalam Kasus Pembunuhan Munir Said Thalib sebagai Pelanggaran Hak Asasi Manusia di Indonesia - Armanda, Saddam Husein; Priyambodo, Mas Agus (HUMANIORUM, 2024)
This scientific law article analyzes the criminal responsibility in the murder case of Munir Said Thalib as a human rights violation in Indonesia. The research aims to evaluate whether Munir's murder meets the criteria for a gross human rights violation under Law Number 26 of 2000 concerning the Human Rights Court, and to identify obstacles and challenges in enforcing justice and uncovering the intellectual authors in this case. The research method used is qualitative with a normative legal approach, relying on primary and secondary data from official documents, supporting literature, and scientific journals. The results indicate that although the field perpetrators have been punished, full accountability, especially from the intellectual authors and potential command responsibility, has not been achieved. Juridical analysis indicates that Munir's murder meets the criteria for a crime against humanity, but the classification and prosecution of this case as a gross human rights violation faces various obstacles, including alleged impunity and weaknesses in the legal framework. The research suggests the need for further investigation, revision of related laws, and increased cooperation between institutions to ensure justice for Munir and prevent similar cases in the future.